PERANAN BEBERAPA JENIS TANAMAN HUTAN KOTA DALAM PENGURANGAN DAMPAK EMISI LOGAM BERAT DI UDARA - Gusmailina Gusmailina (Jurnal Penelitian Hasil Hutan, 1996)
The increase of motorized  vehicles in the city has caused environment problems, especially the air pollution  as  the emission  of gasses  containing  heavy metals such as Pb endangers. Therefore  the selected  of tree city forest  based on  environmental  benefit management  must  be necessary to criteria development forest  city programme.This  article  presents  some  result  of  absorption  and  adsorption  of  Pb  heavy metals  by several plants.  The results showed the Cinnamonunum sp more effective to adsorp the Pb heavy metals  in the air, furthere more Agatliis lorantifolia,  Paraserianthes  falcataria,  and  Swietenia macrophylla.    Whereas Agathis lorantifolia more effectiveto absorp the Pb heavy metals in the air, furthere  more Swietenia macrophylla, Paraserianthes  falcataria, and Cinnamornmum sp.Keywords : Environment, Pb heavy metal, Absorption, Adsorption, Urban forest.